1998
DOI: 10.1148/radiology.209.1.9769829
|View full text |Cite
|
Sign up to set email alerts
|

Chorioamniotic separation after second-trimester genetic amniocentesis: importance and frequency.

Abstract: Small degrees of CAS are frequently present after amniocentesis but are not detected because the membranes are not specifically evaluated. Complete CAS is less frequent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 0 publications
2
47
1
Order By: Relevance
“…Of the 47 reported cases, 29 patients (62%) had amniocentesis; 2 patients (4%) underwent amniodrainage for polyhydramnios [12,14]; 5 patients (11%) had in utero fetal surgery by hysterotomy for diaphragmatic hernia [10]; 1 patient (2%) had chorion villus sampling at 9 weeks of gestation [11], and, finally, 10 cases of CMS (21%) occurred spontaneously, of whom 1 had polyhydramnios associated with encephalocele [12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 47 reported cases, 29 patients (62%) had amniocentesis; 2 patients (4%) underwent amniodrainage for polyhydramnios [12,14]; 5 patients (11%) had in utero fetal surgery by hysterotomy for diaphragmatic hernia [10]; 1 patient (2%) had chorion villus sampling at 9 weeks of gestation [11], and, finally, 10 cases of CMS (21%) occurred spontaneously, of whom 1 had polyhydramnios associated with encephalocele [12].…”
Section: Resultsmentioning
confidence: 99%
“…Two IUFD cases were related to an amniotic band around the cord [10], 1 case was associated with thrombosis of a segment of the cord near the placenta [11], and for the remaining 3 cases, the cause of IUFD was not specified [6,11]. In 6 cases, the pregnancy resulted in a midtrimester miscarriage [6,8,9,11,13,14].…”
Section: Resultsmentioning
confidence: 99%
“…The membranes may be partially separated at one site (partial or focal), they may be completely separated to the insertion of the amnion on the umbilical cord (complete or circumferential). In mild cases, it usually remains subclinical and even unrecognizable on subsequent sonographic examinations (6). However, in cases of severe separation, it is associated with the most significant morbidity and mortality leading to amniotic band syndrome presenting with ligation of umbilical cord and impairment of umbilical blood flow (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…Partial non-fused membranes were included in other studies 2 -4 . The separation required between the two membranes to define CAS has been reported variously as at least 10 mm 5,6 , 3 mm 2,3 or 1 mm 4 . The highest rate of aneuploidy was observed in studies which included only major separation.…”
mentioning
confidence: 99%
“…Isolated CAS was associated more often with an aneuploidy when the separation between the membranes was large (> 10 mm) and complete. Some studies included CAS detected after amniocentesis 1,4 while others included only spontaneous cases 2,3,5 . Levine et al demonstrated that CAS occurring following amniocentesis was often a limited form with no specific consequences on the pregnancy 4 .…”
mentioning
confidence: 99%